Pilot Test of a Culturally Appropriate Diabetes Prevention Intervention for At-Risk Latina Women. (December 2017) - McCurley, Jessica L.; Fortmann, Addie L.; Gutierrez, Angela P.; Gonzalez, Patricia; Euyoque, Johanna; Clark, Taylor; Preciado, Jessica; Ahmad, Aakif; Philis-Tsimikas, Athena; Gallo, Linda C.
Purpose: The purpose of the study was to test the preliminary effectiveness, feasibility, and acceptability of a peer-led, culturally appropriate, Diabetes Prevention Program (DPP)–based lifestyle intervention for Latina women at high-risk for type 2 diabetes (T2DM). Methods: Participants (N = 61) were overweight/obese (body mass index [BMI] ≥25) Latina women with no diabetes, at elevated risk either due to midlife age (45-65 years; n = 37) or history of gestational diabetes mellitus (n = 24). The study used a 1-group pretest-posttest design and offered 12 weeks of peer-led education sessions in a community setting. The intervention targeted physical activity and dietary behaviors to facilitate weight reduction and included culturally appropriate content, age-specific health information, and stress/emotion management strategies. Clinical and self-report assessments were conducted at baseline, month 3, and month 6. Results: Mean participant age was 47.8 years (SD = 10.8). Most (91.2%) were born in Mexico, and 43.3% had a ninth-grade education or less. At month 6, participants achieved a mean reduction of 4.1% body weight (7 lb [3.2 kg]). Statistically significant improvements were observed for dietary behaviors, stress, and depression symptoms. Attrition was low, 5% (3 women). Focus groups indicated that intervention content increased knowledge, was applicable, highly valued, culturally relevant, and would be recommended to others. Conclusions: This culturally tailored DPP adaptation was feasible and acceptable for 2 groups of Latina women at high-risk for T2DM and showed preliminary effectiveness in reducing weight and modifying self-reported dietary behaviors, stress, and depression symptoms. Further research is needed to identify ways to enhance weight loss and diabetes prevention in this at-risk, underserved population.